Assessing public sentiments and news preferences on Al Jazeera and Al Arabiya. (January 2017) - Al-Rawi, Ahmed
This article investigates the online comments made by Arab Facebook users on news items posted on the Facebook pages of two very popular TV channels: Al-Jazeera Arabic and Al-Arabiya. This study employs different methods to closely examine over 620, 000 comments posted on the two Facebook pages as well as studying the most commented on news stories from a total of 11, 685 news reports. The results indicate that commentators expressed some dominant sentiments that are mostly in line with the TV channels' coverage of certain events, while certain news topics attracted most of the online public's comments especially on Al Jazeera channel.